Analisis Perbandingan Kinerja Keuangan Menggunakan Rasio Keuangan Pada Perusahaan Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Qur’ana Asnan, Nanda Nur; Musa, Muh. Ichwan; Nurman, Nurman (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
This study aims to determine the financial performance of the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 5 (five) periods, namely 2016-2020. The research sample was determined by purposive sampling technique as many as 5 companies. The data analysis technique uses profitability ratios, liquidity ratios and solvency ratios. The results showed that based on the profitability ratio of PT. Wilmar Cahaya Indonesia Tbk, PT. Indofood CBP Sukses Makmur Tbk, PT. Mayora Indah Tbk, PT. Sekar Laut Tbk, and PT. Siantar Top Tbk has a financial performance that is in poor condition seen from the average value of NPM and ROE below industry standards. Based on the liquidity ratio of PT. Wilmar Cahaya Indonesia Tbk, PT. Indofood CBP Sukses Makmur Tbk, PT. Mayora Indah Tbk, and PT. Siantar Top Tbk has financial performance that is in good condition seen from the CR and QR values ​​above industry standards. While at PT. Sekar Laut Tbk. have financial performance that is in bad condition. Based on the solvency ratio seen from the DAR value of PT. Wilmar Cahaya Tbk. have financial performance that is in good condition. while judging from the DER value, PT. Wilmar Cahaya Indonesia Tbk., PT. Indofood CBP Sukses Makmur Tbk and PT. Siantar Top Tbk. have financial performance that is in good condition.